PEMBELAJARAN LITERASI DAN NUMERASI MELALUI DEEP LEARNING: PENDEKATAN TRANSFORMASIONAL DI SEKOLAH DASAR - Aryanto, Sani; Meliyanti, Meliyanti; Amelia, Decenni; Maharbid, Dian Anggraeni; Gumala, Yosi; Gildore, Phyll Jhan E. (LPPM Universitas Bina Bangsa, 2025)
Literacy and numeracy are fundamental skills that are crucial for elementary school students in addressing the challenges of the digital era. However, current teaching practices tend to be less effective in fostering deep comprehension. Therefore, the deep learning approach emerges as an alternative that can enhance conceptual understanding in a more profound and sustainable manner. This article aims to examine the implementation of the deep learning approach in literacy and numeracy education at the elementary level through a literature review method. The literature review is conducted by searching, selecting, and critically analyzing academic journals, books, and relevant research reports. The selection criteria for sources include the credibility of the authors, relevance to the topic, and publication within the last ten years. The data analysis technique employed is thematic analysis to identify patterns and conceptual relationships between deep learning and literacy as well as numeracy education at the elementary level. The findings indicate that deep learning can improve students' critical thinking skills, problem-solving abilities, and conceptual understanding. The implications of this study are expected to provide valuable insights for educators in designing more effective teaching strategies.